Hierarchical propagation of structural features in protein nanomaterials. Issue 6 (1st February 2022) - Kamada, Ayaka; Herneke, Anja; Lopez-Sanchez, Patricia; Harder, Constantin; Ornithopoulou, Eirini; Wu, Qiong; Wei, Xinfeng; Schwartzkopf, Matthias; Müller-Buschbaum, Peter; Roth, Stephan V.; Hedenqvist, Mikael S.; Langton, Maud; et al.
Abstract : A hierarchical self-assembly process of proteins spanning six orders of magnitude in size is described. The distinct structural features can be turned on and off by controlling the length distribution of the protein nanofibrils. Abstract : Natural high-performance materials have inspired the exploration of novel materials from protein building blocks. The ability of proteins to self-organize into amyloid-like nanofibrils has opened an avenue to new materials by hierarchical assembly processes. As the mechanisms by which proteins form nanofibrils are becoming clear, the challenge now is to understand how the nanofibrils can be designed to form larger structures with defined order. We here report the spontaneous and reproducible formation of ordered microstructure in solution cast films from whey protein nanofibrils. The structural features are directly connected to the nanostructure of the protein fibrils, which is itself determined by the molecular structure of the building blocks. Hence, a hierarchical assembly process ranging over more than six orders of magnitude in size is described. The fibril length distribution is found to be the main determinant of the microstructure and the assembly process originates in restricted capillary flow induced by the solvent evaporation. We demonstrate that the structural features can be switched on and off by controlling the length distribution or the evaporation rate without losing the functional properties of the protein nanofibrils.